The Process of Creation of Bathymetric Information in Terms of the Set Theory - Kopacz, Z.; Morgaś, W.; Urbański, J. (The International Hydrographic Review, 2015)
All types of bathymetric information and its properties are presented. The entire process of creating bathymetric information, beginning from the planning of the bathymetric survey to the post-processing of bathymetric measurements, is described. This process is expressed in terms of the set theory. Therefore, the description of this very complicated process has become easier and more understandable.